Analisis Disiplin Kerja Guru di SDIT Ash Haabul Kahfi Lubuk Alung Tahun Ajaran 2024/2025 - Ilham Suriadi; Zulfani Sesmiarni; Nasrin Hasibuan (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to determine the level of teacher work discipline at SDIT Ash Haabul Kahfi Lubuk Alung. Work discipline is an important factor in improving the quality of education because it is directly related to the responsibility and professionalism of teachers in carrying out their duties. The method used in this research is a quantitative approach with descriptive techniques. Data were obtained through observation, questionnaires, and documentation, which were then analyzed to see the tendency of teachers' disciplinary behavior. The results showed that the overall level of teacher discipline was in the high category. Teachers at SDIT Ash Haabul Kahfi Lubuk Alung show punctuality, obedience to rules, and consistent execution of tasks. This reflects an effective school management system and teachers' personal commitment to carrying out their professional responsibilities. This good work discipline has a positive impact on the learning environment and supports the achievement of educational goals at school.